Metal Bending Machine for Lighter Projects - Basharie, Siti Mariam (Multidisciplinary Applied Research and Innovation, 2023)
A metal bending machine is one of the machines commonly used in the manufacture of engineering products to shape material into the required shape. This project aims to design a smaller and more compact metal bending device that is able to bend soft metal materials. In this project, a small portable metal bending tool with the size of 400 mm in length and 87.4 mm in height has been designed and manufactured to be able to bend soft metals like mild steel flat bars. This metal bending machine is designed to have a minimal applied force. After conducting several performance tests, the results show that the metal bending machine is capable of producing bending angles on the bending workpiece from an angle of 10° to 60°. This product is small and compact, which makes the machine portable. The machine is simple and easy to operate and it is environmentally friendly because it will not leave any carbon footprint since it does not require fuel or electrical power.